Playing Like a Girl Cindy Blodgett and the Lawrence Bulldogs Season of 93-94 - Tabitha King Mar 42, 1949 (Dendrite Corporation, 1994)
The work is about basketball player Cindy Blodgett during her time at Lawrence High School, Fairfield, ME, 93-94.
Keywords: Cindy Blodgett; Lawrence High School, Fairfield, ME; Women Basketball Players Maine